Short-Duration Aman Rice: The Major Driver for Agricultural Diversification and Intensification in Northern Bangladesh - Ahmed, Sharif; Miajy, Abdullah; Bhandari, Mumnath (International Rice Research Institute, 2024)
The economy of Bangladesh depends on its agricultural sector which contributes to 13% of the country's GDP. Food security is heavily reliant on rice production here, as rice serves as a staple food and the main source of calories, with 75% of the country's land dedicated to rice cultivation. To cope with the challenges of climate change and agricultural transformation, Bangladesh needs to diversify its crop production. There is a tradeoff between crop diversification and food security in Bangladesh; therefore, cropping intensification is the best solution for crop diversification. From June to September/October, the wet season poses significant challenges for diverse crop cultivation due to frequent rain and wet soil conditions, making Aman rice the most viable and profitable choice for farmers during this period. The best option for crop diversification here is the dry season (October/November to May/June) but the cultivation of Boro rice within this dry season window is a major challenge to provide space for non-rice crops. Boro rice contributes around 55% of rice production in Bangladesh, playing a significant role in the country's food security. By default, Aman is the primary crop in the wet season, but several challenges are associated with this (flood, storm, drought, etc.).